2018
DOI: 10.21873/anticanres.12399
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Multicenter Study of Carbon Ion Radiotherapy for Locally Advanced Olfactory Neuroblastomas

Abstract: Abstract. The purpose was to evaluate efficacy and safety of carbon ion radiotherapy (C-ion RT) in patients with locally advanced olfactory neuroblastomas (ONBs). This study was a sub-analysis of the Japan Carbon-Ion Radiation Oncology Study Group Study (1402 HN, UMIN000024473). Clinical data of T4 ONBs treated with C-ion RT at fourOlfactory neuroblastoma (ONB) of the head and neck is a rare malignant tumour that arises from the olfactory neuroepithelium in the upper nasal cavity with extension into the skull … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…Most of the published cases are described in case studies or a single-institution’s retrospective analyses with small cohorts. To our knowledge, the biggest cohorts describing particle therapy in the treatment of ENB consist of 42 patients treated with protons from 1999 to 2012 [ 22 ] and 21 patients treated with carbon ions from 2003 to 2014 [ 23 ]. Generally, the biggest patient cohorts are known from database analyses, in which different radiation techniques are usually not further described, for example, recently in a National Cancer Database analysis investigating 931 cases of ENB [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published cases are described in case studies or a single-institution’s retrospective analyses with small cohorts. To our knowledge, the biggest cohorts describing particle therapy in the treatment of ENB consist of 42 patients treated with protons from 1999 to 2012 [ 22 ] and 21 patients treated with carbon ions from 2003 to 2014 [ 23 ]. Generally, the biggest patient cohorts are known from database analyses, in which different radiation techniques are usually not further described, for example, recently in a National Cancer Database analysis investigating 931 cases of ENB [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For central nervous system necrosis induced by CIRT, a previous study demonstrated that the brain volume receiving >50 Gy was a significant risk factor for the development of grade 2 or higher radiation-induced brain injury . 20 Future studies should focus on using new technical methods such as scanning irradiation or intensity-modulated particle therapy, since they improve dose distribution [21][22][23] and may therefore reduce the incidence of central nervous system necrosis. Meanwhile, our results demonstrated that there was no grade 2 or higher osteoradionecrosis, although Koto et al reported grade 3 temporal bone necrosis with skin ulcers in two patients receiving CIRT .…”
Section: T a B L E 3 Univariate Analysis For Localmentioning
confidence: 99%
“…Our multicenter study (J-CROS 1402 HN) showed that CIRT was effective and safe for head and neck malignancies, particularly including radioresistant tumors. [9][10][11][12][23][24][25] Since April 2018, the public health insurance system in Japan has covered CIRT for head and neck malignancies, with the exception of radiosensitive oral, laryngeal, and pharyngeal squamous cell carcinoma.…”
Section: T a B L E 3 Univariate Analysis For Localmentioning
confidence: 99%
“…Non-squamous cell carcinoma (NSCC) in the head and neck region is resistant to photon therapy and chemotherapy, and therefore the standard therapy for this disease remains a subject of debate. Previous studies indicated that carbon-ion radiotherapy provides favorable local control and survival for head and neck NSCCs [1][2][3][4]. Differing from squamous cell carcinomas of the head and neck region, which are predominantly located in the oral cavity and pharynx, more than 50% of NSCCs arising in the head and neck region are located in the sinonasal cavity [5].…”
mentioning
confidence: 99%
“…Cumulative incidence of Grade 1 or higher nasolacrimal duct obstruction stratified by (a) a V40 value of 0.08 cm3 , or (b) primary tumor site. P-values calculated by log-rank test are shown.…”
mentioning
confidence: 99%